Should Older Teens and Young Adults With Chronic, Life-Threatening Pediatric Illnesses be Transitioned to Adult Providers and Care Based on Chronologic Age?. Issue 3 (May 2015) - Capitulo, Kathleen Leask; McCarthy, Colleen; McKie-Addy, Cynthia
Abstract : When is the best time to transition care of teens and young adults with chronic healthcare conditions to adult providers?